Pelindungan Hukum Terhadap Pemegang Polis Akibat Pelanggaran Prinsip Utmost Good Faith yang Dilakukan oleh Perusahaan Asuransi Dalam Penutupan Polis Asuransi Jiwa (Studi Putusan Nomor 135/Pdt.G/2022/Pn Jkt.Sel) - L, Lesli; S, Saidin; M, Mulhadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This scientific paper aims to analyze the legal protection for policyholders in the context of violations of the principle of utmost good faith committed by insurance companies during the conclusion of life insurance policies. The principle of utmost good faith is a crucial foundation in the relationship between insurance companies and policyholders, requiring both parties to act honestly and transparently. This research utilizes a case study from Decision No. 135/Pdt.G/2022/PN Jkt.Sel, which illustrates how violations of this principle can impact the rights of policyholders. The findings indicate that violations of the utmost good faith principle can result in losses for policyholders, both financially and legally. Furthermore, the court's decision in this case study provides an important precedent regarding the responsibility of insurance companies and the legal protections available to policyholders. Thus, this paper emphasizes the importance of awareness of the legal rights of policyholders and the necessity for stricter regulations to protect the interests of clients within the insurance industry.